Peran Pembina Sekolah Minggu Bagi Masa Depan Pemimpin Gereja - Rikus, Rikus (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2023)
A good coach is a coach who thinks about the progress of the people he coaches because that is the goal of a coach, namely to advance the children he coaches. Sunday school leaders are very important in preparing the next generation of church leaders so that the church remains strong and even continues to bring good news to people who do not yet know the Lord God. A coach must prepare himself well so that when he becomes a coach he is not surprised by the situation that occurs. A coach who is truly ready to become a coach for children is someone who has a good relationship with God so that he can be an example for the children he coaches so that what they learn from their coach can be useful for them in the future when they become leaders in the church. The purpose of writing this article is to understand the importance of properly nurturing the next generation of children; can help readers understand that nurturing a generation of children is very important. The method used to write this article is qualitative literature study sourced from books, articles, the Bible and magazines that contain children. This research makes churches increasingly prepare the best child coaches who are committed and care about the generation of children they coach so that the main goal in coaching this generation of children can be achieved because the coaches truly rely on the Lord Jesus.